(untitled) (Asian Business Research, 2016)
Computer-based algorithms & models have become important in trading in financial markets. We illustrate the significance of model analysis of financial systems by a case study of BlackRock’s analytical platform called ‘Aladdin’. The nature of the model used in a computer algorithm is central to its real performance. Unreal models in financial algorithms will yield inaccurate performances. We review five fundamental models of economic dynamics: (1) traditional price-equilibrium of a commodity market, (2) Keynes-Minsky financial transactions over time, (3) price-disequilibrium of a financial market, (4) investment bank market disequilibrium process, and (5) disequilibrium financial grid of international capital flows. Empirically-valid graphic models are necessary – in order to methodologically develop societal-useful normative economic theory – based upon the real natural-experiments of societies in economic history.